2008
DOI: 10.1007/s00011-008-8031-8
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte depletion during cardiac surgery with extracorporeal circulation in high risk patients

Abstract: Interestingly, the activation of neutrophils was more pronounced in the LF group. The use of a leucocyte depleting filter was not advantageous for this patient cohort for clinical or biomedical endpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…In addition to local effects of cell adhesion / activation systemic clinical consequences that have been directly related to leukocyte activation include infection, myocardial infarction as well as organ injury and failure [80,118]. Leukocyte removal filters have been introduced in cardiopulmonary bypass (CPB) [119] yet released inflammatory mediators from the trapped cells could contribute to the inflammatory response [120].…”
Section: Follow-on Commentsmentioning
confidence: 99%
“…In addition to local effects of cell adhesion / activation systemic clinical consequences that have been directly related to leukocyte activation include infection, myocardial infarction as well as organ injury and failure [80,118]. Leukocyte removal filters have been introduced in cardiopulmonary bypass (CPB) [119] yet released inflammatory mediators from the trapped cells could contribute to the inflammatory response [120].…”
Section: Follow-on Commentsmentioning
confidence: 99%
“…Bakhtiary et al discovered a positive correlation between the level of leukocytes and inflammation. Their research showed that the depletion of leukocytes caused the reduction of inflammatory response [ 21 ]. Based on these results and our statistical data, we speculated that the percentage of neutrophil and WBC may be used to predict AGC.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that leukocyte depletion was not advantageous from clinical and biomedical end points in the patient group studied. 27 The use of cell-saving devices in the setting of CPB is still controversial. 28 Two major prospective randomized double-blind trials assessing the use of a cell-saving device yielded different results.…”
Section: Avoiding Stroke By Modifying the Surgical Approachmentioning
confidence: 99%